2017
DOI: 10.19082/5732
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cardiac functions in children with Duchenne Muscular Dystrophy: A prospective case-control study

Abstract: BackgroundDuchenne muscular dystrophy (DMD) is the most common childhood form of muscular dystrophy. The incidence of cardiomyopathy in DMD increases with age, so its early detection is important because institution of cardioprotective medical therapies may slow adverse remodeling and attenuate heart failure symptoms in these patients.ObjectiveTo assess the cardiac functions in children clinically suspected to have DMD.MethodsOver a one-year period, 28 male children aged from 3 to 18 years old, who met the cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Both lower contraction force and arrhythmic events occur in DMD patient's heart from a very young age and before dilated cardiomyopathy onset. In fact, 25% of pediatric DMD patients under 10 years old already showed decreased ejection fraction and have developed sinus tachycardia (Sadek et al, 2017). Overall, our model presents functional alterations of an early-stage cardiac manifestation of DMD.…”
Section: Discussionmentioning
confidence: 73%
“…Both lower contraction force and arrhythmic events occur in DMD patient's heart from a very young age and before dilated cardiomyopathy onset. In fact, 25% of pediatric DMD patients under 10 years old already showed decreased ejection fraction and have developed sinus tachycardia (Sadek et al, 2017). Overall, our model presents functional alterations of an early-stage cardiac manifestation of DMD.…”
Section: Discussionmentioning
confidence: 73%
“…In particular, we defined cardiomyopathy with values of left ventricular ejection fraction (EF) and shortening fraction (SF) of, respectively, <55 or <28% or both, while severe cardiomyopathy was considered with EF <45% and SF <20%. Severe pulmonary disease was determined by Forced Expiratory Volume in 1 s (FEV 1 ) <0.8 L and Force Vital Capacity (FVC) <40% (3840). Included DMD patients' genotyping showed deletion of N -terminal ( N = 3), ROD domain ( N = 8), and point mutation of ROD domain ( N = 1) of dystrophin gene.…”
Section: Methodsmentioning
confidence: 99%
“…After muscle injury, the plasma level of the aforementioned CK and LDH is increasing [ 135 , 136 , 137 ]. Sadek et al’s (2017) [ 93 ] study on DMD children showed that creatinine phosphokinase (CPK) in all cases was high and in 19 cases of 28 male DMD children, the LDH level was also elevated, in comparison to control individuals.…”
Section: Common Genesmentioning
confidence: 99%